Estação Memória Paraisópolis e as relações entre informação, memória e experiência - Borges Paiva , Simone (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Paraisopolis’s Memory Station aims to reaffirm inextricable bonds existing between information and signification, fostering objective conditions of dialogue amongst the past and the present. In this paper, we present the construction process of a apparatus named Paraisopolis’s Memory Station with the community in Paraisópolis, the second largest favela of São Paulo, its history and memory of their residents, have provided the basis for our early scientific questions which aimed to understand the the apparatus Memory Station as a stimulator of appropriation processes and the cultural protagonism. The collaborative methodology allowed to integrate with the community, as well as, the implementation of weekly intergenerational meetings called Memory Workshops, the photo's exhibits and a creation of a data base for storage, preservation and socialization of content.
Keywords: Paper Model; Scientific Paper; Author’s Instructions